Realistic mathematics education and mathematical literacy: a meta-analysis conducted on studies in Indonesia - Putri, Amelia Defrianti; Juandi, Dadang; Turmudi, Turmudi (Intelektual Pustaka Media Utama, 2024)
A considerable body of literature exists pertaining to realistic mathematics education (RME) and its correlation with mathematical literacy, with numerous studies demonstrating incongruent results. The principal objective of this meta-analysis is to systematically investigate the overarching influence of RME on mathematical literacy within the context of Indonesia. The collection of documents comprises a total of seventeen publications that were released between the years 2014 and 2023. The estimation methodologies utilized in this study were grounded on a random-effects model, and statistical computations were conducted utilizing the comprehensive meta-analysis (CMA) software in academic writing. The equation proffered by Hedges was employed for the quantification of effect magnitude. The outcomes of the investigation reveal that the implementation of RME learning yielded a noteworthy and advantageous impact (effect size = 1.031; p 0.05) on the adeptness of students in the domain of mathematical literacy. Moreover, many moderating factors, including class capacity, educational level, geographical location, content of the Programme for International Student Assessment (PISA), and the combination of learning, did not significantly impact students' diverse mathematical literacy proficiency. This study proposes that mathematics educators should consider utilizing the RME as a means of improving students' proficiency in mathematical literacy.